Roland Barthes : pour une écologie de l’écriture - Matei, Alexandru (Labyrinth, 2020)
Even if the theoretical prestige of the notion of ecology is recent, an ecological writing has already been racticed, without receiving this name, by Roland Barthes. On several occasions, progressively after Writing Degree zero (1953), Roland Barthes envisaged writing as a multifaceted practice, the most suitable for overturning the only order worth to be revolutionized, the symbolic order. We will take a fresh look at Barthes' writing as a theoretical concept in the early 1950s, along a shift that takes the term first to the name of a technique. Finally, in the mid-1970s, writing comes to be defined by Barthes as a practice that ignores the dichotomy between matter or body and mind or idea, and which arrives, in a spiral return movement, at an inclusive conception that recovers both the concept and the practice. This is where writing meets, in Barthes' work, the act that Latour calls "greening" and which he defines above all as a new relationship between facts and values. In the light of the latest research in "Barthesian studies" we would like to show that the future of "theory", if it is ecology today, lies in the practice and ecological commitment of writing, as a mediator of meaning, a tool of "charitable fiction", at the confines of spirit and matter.